Comparisons of the effects on satiety and eating behaviour of infusion of lipid into the different regions of the small intestine. Issue 3 (March 1988) - Welch, I M; Sepple, C P; Read, N W
Abstract : Food intake and feelings of hunger and fullness were monitored in paired studies carried out in two groups of six healthy non-obese male volunteers during infusion of isotonic solutions of either a 50% corn oil emulsion or saline into the jejunum or into the ileum. Infusion of the lipid emulsion at a rate of 1.2 ml/min (4.9 kcal/min) into either the ileum or the jejunum significantly reduced the period of eating (p less than 0.01) and the quantity of food consumed (p less than 0.01), but neither affected the rates of drinking or the amount of fluid consumed. Infusion of the lipid emulsion into the jejunum also significantly reduced the sensations of hunger before the meal (p less than 0.05), and the rate of ingestion (p less than 0.01). Ileal infusion did not influence these indices. The results suggest that jejunal and ileal infusion of lipid reduces the size of the meal that could be consumed possibly by inhibiting gastric emptying. The alleviation of hunger before ingestion and the slower rate of eating, however, suggests that jejunal lipid activates an additional mechanism that influences the appetite centre in the hypothalamus directly.